2014
DOI: 10.1167/iovs.14-14152
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Oxygen Saturation Increases After Vitrectomy

Abstract: Retinal arterial and venous oxygen saturation are significantly increased after vitrectomy, while the AVD is decreased after vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…), and a similar study was published in the same year (Lim et al. ). The latter described an increase in oxygen saturation in both artery and vein after phacovitrectomy.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…), and a similar study was published in the same year (Lim et al. ). The latter described an increase in oxygen saturation in both artery and vein after phacovitrectomy.…”
Section: Introductionmentioning
confidence: 53%
“…In the Lim et al. () study, all patients underwent both PPV and phacoemulsification. In our study, there is a different trend between the subgroups according to the lens status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, oxygen saturation increased postoperatively by 2.8% in arteries and by 9.0% in veins, leading to a reduction in the A-V difference of 6.2%. With the use of the Oxymap T1, Lim et al7 and Šín et al8 reported similar findings that the retinal arterial and venous oxygen saturation were significantly increased after vitrectomy, leading to a decrease in the A-V difference. Based on previous reports and our current findings, retinal oxygen saturation increased in retinal arteries and further increased in retinal veins, and consequently, the A-V difference decreased.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, previous studies have indicated that retinal oximetry is influenced by age, gender, and ethnicity (fundus pigmentation). Several investigators have reported the change in the retinal oximetry using the Oxymap T1 after vitreous surgery 7,8. To date, however, there is insufficient evidence with regard to the effect vitreous surgery has on retinal oximetry.…”
Section: Introductionmentioning
confidence: 99%